Stephanus the philosopher and physician : commentary on Galen's Therapeutics to Glaucon - Stephanus, of Athens. (Studies in Ancient Medicine, 1998)
This volume is an edition of the Commentary by Stephanus of Athens, the seventh-century physician and philosopher, on book One of Galen's Therapeutics to Glaucon . It comprises introduction, Greek text with critical apparatus and index of sources, English translation, notes, bibliography, and index. As one of the few medical texts to date from this period, and one of the most detailed and complete, the commentary sheds important light on the nature and extent of medical education in the West, on the eve of the Arab conquest.